Manipulation of Communication - Alli, Suhaimah (WritingThreeSixty, 2025)
J. M. Coetzee’s Disgrace highlights many issues within universities and across South Africa through his character David Lurie. Lurie’s plethora of opinions is readily available throughout the novel in tightly packaged poetic verses or decorated words of wisdom borrowed from Byron. His tactful usage and deliverance of language will be highlighted in this essay with the aim of showing how Lurie manipulates language in communicative events to evade accountability regarding his and Melanie’s affair. This essay aims to question whether Lurie intended to communicate or manipulate both the characters and the readers.